2014
DOI: 10.1007/82_2014_397
|View full text |Cite
|
Sign up to set email alerts
|

The Effector T Cell Response to Influenza Infection

Abstract: Influenza virus infection induces a potent initial innate immune response, which serves to limit the extent of viral replication and virus spread. However, efficient (and eventual) viral clearance within the respiratory tract requires the subsequent activation, rapid proliferation, recruitment, and expression of effector activities by the adaptive immune system, consisting of antibody producing B cells and influenza-specific T lymphocytes with diverse functions. The ensuing effector activities of these T lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 154 publications
(211 reference statements)
1
92
0
Order By: Relevance
“…In contrast, NP vaccinated cohorts of aged mice did not show any significant enhancement of CD4 T cell numbers in either spleen or lungs when compared to controls. Importantly, it is essential for these vaccine generated CD4 T cells to be recruited to the lungs during influenza infection in order to quickly and completely clear virus and resolve inflammation [31] and the lack of NP-specific T cells in the aged lungs could be a major contributor to slower resolution of infection.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, NP vaccinated cohorts of aged mice did not show any significant enhancement of CD4 T cell numbers in either spleen or lungs when compared to controls. Importantly, it is essential for these vaccine generated CD4 T cells to be recruited to the lungs during influenza infection in order to quickly and completely clear virus and resolve inflammation [31] and the lack of NP-specific T cells in the aged lungs could be a major contributor to slower resolution of infection.…”
Section: Resultsmentioning
confidence: 99%
“…In our studies, we observed that the virus-infected P2X7r KO mice had lower levels of proinflammatory cytokines such as IL-6, TNF-α, IFN-γ, CXCL10, and CCL2 in their lungs at day 3 postinfection. Activation of P2X7 receptors by extracellular ATP plays a central role in the release of proinflammatory cytokines, and it plays a role on the regulation of macrophages, neutrophils, and effector T cells, important cell mediators during inflammation (9, 11, 53, 54). Therefore, the lower level of cytokines observed in the lungs of the P2X7r KO mice after influenza virus infection may be explained by the lack of activation of this purinergic signaling pathway in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be explained by the time when we measured IL-10 in the lungs, since the main contributors to IL-10 production in the context of influenza infection are CD8 + effector T cells, a population of cells that is found later in infection (41). In addition, increased levels of this cytokine early during infection can hinder the activation of the antiviral immune response (53), suggesting that the increased levels observed in the WT mice early during infection may be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α can be produced by different cell types after influenza infection, including TNF/iNOS-producing DCs (tipDCs) [42], lung epithelial cells [43], and helper T cells and cytotoxic T lymphocytes [44]. TNF-α is considered to be the prototypical proinflammatory cytokine at the “center of the influenza cytokine storm”, escalating the severity of disease in humans with highly pathogenic and pathological influenza infections[45] [46] [47].…”
Section: Cytokines Directly Induced By Viral Infection (Primary Cytokmentioning
confidence: 99%